Nitrofurantoin Induced Reversible Interstitial Lung Disease - Ashraf, Shabana; Salahudheen, Sajid (Indian Journal of Pharmacy Practice)
Drug-induced interstitial lung disease is an increasingly common cause of morbidity and mortality. Nitrofurantoin is a broad-spectrum antibiotic used for acute uncomplicated or simple cystitis as well as for prophylaxis of recurrent infection. We recently encountered a case of Nitrofurantoin-induced interstitial lung disease in an elderly patient who was on Nitrofurantoin for a year and a half for recurrent urinary tract infections. On further evaluation, she was diagnosed with drug-induced interstitial lung disease, which was confirmed by radiographic evidence. Nitrofurantoin was discontinued and managed with low-dose systemic glucocorticoids. This case report highlights the need for close vigilance of pulmonary toxicities in patients taking long-term Nitrofurantoin therapy.
Keywords: Pulmonary toxicity; Corticosteroids; Nitrofurantoin; Interstitial Lung disease; Urinary tract infection